The Sources of American Conduct : A Contribution to the Debate about the Transantlantic Difference (Czech Journal of International Relations, 2003)
Is the American unilateralism after 9/11 fueled by a realization of America's unequalled military might in the world, or is it an expression of America's cultural identity? The former explanation tends to describe the current American policy as "realist", the latter describes it as "idealist". This article argues that these two explanations may complement each other if we conceive of current American discourse as a combination of the "vulgar realism of force" and the "substantive idealism of good". This synthesis of realism and idealism gravitates towards the idealistic pole since it is motivated by a profoundly idealistic desire to flee from "the autonomy of the political", defended by classical realists from Machiavelli to Nietzsche and from Schmitt to Morgenthau and Kissinger. Rather than as a realm of pure force, these thinkers conceived politics as a twilight zone between enforcement and persuasion, violence and reason. It is this concept of politics, which is retained by liberal opponents of the current unilateralist course. They combine the "classical realism of force and consent" with the "proceduralist idealism of right". Both idealist neoconservatives and realist liberals are tapping the sources contained in American identity. The outcome of their struggle is, therefore, open.